Maternal Zika Virus Infection: Association With Small-for-Gestational-Age Neonates and Preterm Birth. Issue 6 (December 2019) - Cooper, Hannah J.; Iwamoto, Martha; Lash, Maura; Conners, Erin E.; Paladini, Marc; Slavinski, Sally; Fine, Anne D.; Kennedy, Joseph; Heinke, Dominique; Ciaranello, Andrea; Seage, George R.; Lee, Ellen H.
Abstract : OBJECTIVE: To evaluate whether antenatal Zika virus infection is associated with risk of having a small-for-gestational-age (SGA) neonate, risk of preterm birth, and lower mean birth weight of term neonates. METHODS: For this retrospective observational study, we linked birth record data for women who delivered liveborn singleton neonates in New York City in 2016 to data for pregnant women with Zika virus infection reported to the New York City Health Department. We restricted the analysis to nonsmoking, nonwhite women and adjusted for maternal characteristics. Among women with antenatal Zika virus infection, we used modified Poisson regression to assess risks of having an SGA neonate and of delivering preterm, and linear regression to assess the association of infection with mean birth weight of term neonates. RESULTS: Of 116, 034 deliveries of singleton neonates in New York City in 2016, 251 (0.2%) were to women with antenatal Zika virus infection. A higher percentage of women with Zika virus infection delivered an SGA neonate compared with those without (11.2% vs 5.8%; adjusted relative risk [RR] 1.8; 95% CI 1.3–2.6). There was no difference in preterm birth prevalence for women with and without Zika virus infection (adjusted RR 1.0; 95% CI 0.69–1.6). Mean birth weight of term neonates born to women with Zika virus infection was 47 g less (95% CI −105 to 11 g); this difference was not statistically significant in crude or adjusted analyses. CONCLUSION: For a cohort of New York City women, antenatal Zika virus infection was associated with an increased risk of having an SGA neonate, but not preterm birth or lower mean birth weight of term neonates. This supports a putative association between Zika virus infection during pregnancy and SGA. Abstract : Maternal Zika virus infection was associated with increased risk of small-for-gestational-age neonates but not with preterm birth in a cohort of New York City women.